Attention Guides the Motor-Timing Strategies in Finger-Tapping Tasks When Moving Fast and Slow - Guérin, Ségolène M. R.; Boitout, Juliette; Delevoye-Turrell, Yvonne N. (Frontiers in Psychology, 2021)
Human beings adapt the spontaneous pace of their actions to interact with the environment. Yet, the nature of the mechanism enabling such adaptive behavior remains poorly understood. The aim of the present contribution was to examine the role of attention in motor timing using (a) time series analysis, and (b) a dual task paradigm. In a series of two studies, a ﬁnger-tapping task was used in sensorimotor synchronization, with various tempi (from 300 to 1100 ms) and motor complexity (one target vs. six targets). Time series analyzes indicated that two different timing strategies were used depending on the speed constraints. At slow tempi, tapping sequences were characterized by strong negative autocorrelations, suggesting the implication of cognitive predictive timing. When moving at fast and close-to-spontaneous tempi, tapping sequences were characterized by less negative autocorrelations, suggesting that timing properties emerge from body movement dynamics. The analysis of the dual-task reaction times conﬁrmed that both the temporal and spatial constraints impacted the attentional resources allocated to the ﬁnger-tapping tasks. Overall, our work suggests that moving fast and slow involve distinct timing strategies that are characterized by contrasting attentional demands.